Use efficiency of dynamic stabilizer in the post-repair period of railways in Ukraine - Chernyshova, O. S.; Umanov, M. I.; Kovalev, V. V.; Markov, Y. S.; Gubar, O. V. (Science and Transport Progress, 2013)
Purpose. To analyze the interaction forces of the track and rolling stock at application of dynamic stabilizers, as well as the determination of the area, on which the track stabilization is necessary not only according to the technical indices but also according to the economic ones. Methodology.To achieve the research purpose the methods of analysis of material flows, peculiar to the places that need applications of dynamic stabilizers on railway transport tracks are used. Findings. Researches of relatively economic efficiency of dynamic stabilizers application, which were conducted by scientists during the last years, do not spread to comparison of cost of works on the track stabilizing and losses of railway for period of running. During the running period the trains move with a limited speed that causes corresponding financial losses. Speed limitation result in the both the motion time increase and in some occasions in the heavy consumption of fuel and energy resources. The more intensive track discord and expenses increase for its maintenance are observed in the sections of braking and acceleration immediately in front of and after the areas of limitation. The methodology relative to the estimation of economic efficiency of dynamic stabilizers application after completion of track repairs for the areas of Ukrainian railways with different operational conditions was developed. This methodology includes the losses calculation of railroad, which are predefined by extra motion time, heavy consumption of fuel and energy resources and charges for current maintenance. Originality. The methodology of cost effectiveness evaluating of the dynamic stabilizers application in the post-repair period was developed. Such an approach would allow one to take the rational decisions taking into account the features of the track sections, which were reconstructed. Practical value. The obtained results will rationally assign the works on the dynamic track alignment accounting the operational characteristics of the railway sections and the economic feasibility of the planned works completion.